Could Heme Oxygenase-1 Be a New Target for Therapeutic Intervention in Malaria-Associated Acute Lung Injury/Acute Respiratory Distress Syndrome? - Pereira, Marcelo L. M.; Marinho, Claudio R. F.; Epiphanio, Sabrina (Frontiers in Cellular and Infection Microbiology, 2018)
Malaria is a serious disease and was responsible for 429,000 deaths in 2015. Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is one of the main clinical complications of severe malaria; it is characterized by a high mortality rate and can even occur after antimalarial treatment when parasitemia is not detected. Rodent models of ALI/ARDS show similar clinical signs as in humans when the rodents are infected with murine Plasmodium. In these models, it was shown that the induction of the enzyme heme oxygenase 1 (HO-1) is protective against severe malaria complications, including cerebral malaria and ALI/ARDS. Increased lung endothelial permeability and upregulation of VEGF and other pro-inflammatory cytokines were found to be associated with malaria-associated ALI/ARDS (MA-ALI/ARDS), and both were reduced after HO-1 induction. Additionally, mice were protected against MA-ALI/ARDS after treatment with carbon monoxide- releasing molecules or with carbon monoxide, which is also released by the HO-1 activity. However, high HO-1 levels in inflammatory cells were associated with the respiratory burst of neutrophils and with an intensification of inflammation during episodes of severe malaria in humans. Here, we review the main aspects of HO-1 in malaria and ALI/ARDS, presenting the dual role of HO-1 and possibilities for therapeutic intervention by modulating this important enzyme.